Explanations in sociosyntactic variation - Christensen, Tanya 1974-; Jensen, Torben Juel 1973- (Studies in language variation and change, 2022)
What explains variation in human language? How are linguistic and social factors related? How do we examine possible semantic differences between variants? These questions and many more are explored in this volume, which examines syntactic variables in a range of languages. It brings together a team of internationally acclaimed authors to provide perspectives on how and why syntax varies between and within speakers, focusing on explaining theoretical backgrounds and methods. The analyses presented are based on a range of languages, making it possible to address the questions from a cross-linguistic perspective. All chapters demonstrate rigorous quantitative analyses, which expose the conditioning factors in language change as well as offering important insights into community and individual grammars. It is essential reading for researchers and students with an interest in language variation and change, and the theoretical framework and methods applied in the study of how and why syntax varies